Tantangan dan Peluang Pendidikan Islam pada Era Milenial - Ahmad Husein Ritonga; Fahmi Bafadhal (INNOVATIO: Journal for Religious Innovation Studies, 2018)
The millennial era presents new challenges and opportunities in the field of education. Information technology is a marker. Post modern culture and information globalization interact and have been integrated in education. Even though the millennial era has had a positive impact, this era is also closely related to work ethic, ethics and moral issues. The ease of information and technology that gives birth to laziness, not thinking deeply, not down to earth or not caring about the environment, tend to want to be free, westernized, and sometimes violate ethics. This paper through the author's reflection on the literature relating to Islamic education, aims to unravel the challenges and opportunities of Islamic education in the millennial era. The opportunity for Islamic education based on the integralism spirit of education is increasingly greater to be the main choice of this millennial era education, even though the challenges that will be faced are also getting harder.